DETERMINAN YIELD SURAT BERHARGA NEGARA INDONESIA - Adhiguna, Yasinta (Media Ekonomi, 2024)
This study aims to determine what macroeconomic variables affect the yield of Indonesian Government Securities (SBN). Because in the State Budget (APBN), SBN yield is one of the components that make up the figure on Debt Interest Expenditure, it is important to understand variables that influenced the yield. This study makes use of the Error Correction Model (ECM) analysis method, which may give an overview of the relationship between the independent and dependent variables both in the short and long term. Monthly time series data from 2010 to 2022 are used in this study. The yield of the 10-year tenor SBN denominated in rupiah is the dependent variable. The CPI, foreign exchange reserves, exchange rate, and Bank Indonesia interest rate (BI-Rate) are the independent variables that are employed. Information is taken from Bank Indonesia and Bloomberg. In the short term: Inflation has an insignificant positive effect, BIRATE has an insignificant positive effect, the exchange rate has a significant positive effect, and foreign exchange reserves have a significant negative effect on the 10-year SBN yield. In the long term: inflation has an insignificant positive effect, BIRATE has a significant positive effect, exchange rates have a significant positive effect, and foreign exchange reserves have an insignificant negative effect on the 10-year SBN yield